2022
DOI: 10.1038/s42003-022-03105-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrated multiple driver mesocosm experiment reveals the effect of global change on planktonic food web structure

Abstract: Global change puts coastal marine systems under pressure, affecting community structure and functioning. Here, we conducted a mesocosm experiment with an integrated multiple driver design to assess the impact of future global change scenarios on plankton, a key component of marine food webs. The experimental treatments were based on the RCP 6.0 and 8.5 scenarios developed by the IPCC, which were Extended (ERCP) to integrate the future predicted changing nutrient inputs into coastal waters. We show that simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…In line with this, cells with lower C content might be smaller and likely to have lower sinking velocities and also to become better prey, especially for microzooplankton, which again will feed more carbon into the microbial loop (Legendre and Le Fèvre 1995; Morán et al 2010; Hillebrand et al 2022). Similar results were obtained in a mesocosm experiment during which plankton communities were subjected to simultaneous changes in temperature, p CO 2 , and N : P ratios (Moreno et al 2022), and which identified an intensification of the microbial loop. Evidence have been also found that higher DOC availability (Hitchcock et al 2010) and warming (Hoppe et al 2002, 2008) lead to a higher abundance of bacterioplankton.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with this, cells with lower C content might be smaller and likely to have lower sinking velocities and also to become better prey, especially for microzooplankton, which again will feed more carbon into the microbial loop (Legendre and Le Fèvre 1995; Morán et al 2010; Hillebrand et al 2022). Similar results were obtained in a mesocosm experiment during which plankton communities were subjected to simultaneous changes in temperature, p CO 2 , and N : P ratios (Moreno et al 2022), and which identified an intensification of the microbial loop. Evidence have been also found that higher DOC availability (Hitchcock et al 2010) and warming (Hoppe et al 2002, 2008) lead to a higher abundance of bacterioplankton.…”
Section: Discussionsupporting
confidence: 80%
“…Evidence have been also found that higher DOC availability (Hitchcock et al 2010) and warming (Hoppe et al 2002, 2008) lead to a higher abundance of bacterioplankton. Nevertheless, clearer effects on bacteria abundance might be seen after phytoplankton reach the stationary phase and nutrient depletion, when bacteria abundance increases considerably (Moreno et al 2022). These results highlight the sensitivity of microalgal physiology to the combined effects of multiple drivers.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the combined effects of ocean acidification and food availability has been little examined. It has been suggested that the OA effects could be species-specific in heterotrophic dinoflagellates (Meunier et al, 2017;Moreno et al, 2022) and other zooplankton grazers (Crook et al, 2013;Hurst et al, 2017;Li et al, 2017;Brown et al, 2018). In the present study, no interactive effects between food availability and OA were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive ocean acidification is suggested to affect zooplankton directly due to acidic stress and indirectly because of altered phytoplankton food quality (Jin et al, 2015). Results from mesocosm experiments using field plankton communities showed that OA negatively affected microzooplankton in coastal waters (Park et al, 2014;Horn et al, 2020;Spisla et al, 2021), though opposite results were reported in another study conducted in the coastal North Sea (Moreno et al, 2022). While decreased pH had no detectable effect on the growth and grazing of microzooplankton communities (Suffrian et al, 2008;Aberle et al, 2013;Horn et al, 2016;Wang et al, 2019), it has little been documented on how heterotrophic dinoflagellates respond to OA.…”
Section: Introductionmentioning
confidence: 94%
“…Human activities have led to climate warming and ocean acidification in combination with various pollutants that are continuously added to the oceans (Doney et al, 2012). Those environmental stressors have the potential to affect copepod species abundances and impede topdown and bottom-up planktonic food web structures (Garzke et al, 2016;Cole et al, 2019;Moreno et al, 2022).…”
Section: Introductionmentioning
confidence: 99%